Platelet activation, coagulation and angiogenesis in breast and prostate carcinoma - Caine, Graham J.; Lip, Gregory Y. H.; Stonelake, Paul S.; Ryan, Peter; Blann, Andrew D. (Thrombosis and Haemostasis, 2004)
In health, haemostasis and angiogenesis are tightly regulated processes, but may become deregulated in cancer. Recent evidence suggests that platelet activation may link these processes as platelets can release angiogenic factors such as vascular endothelial growth factor (VEGF). Furthermore, inflammation has also been implicated in regulating both coagulation and angiogenesis, possibly by activating platelets directly and increasing, for example, plasma fibrinogen. We hypothesized relationships between plasma markers of the processes in two common forms of cancer. Plasma levels of VEGF (reflecting angiogenesis), soluble P-selectin, (marking platelet activation), tissue factor [TF], fibrinogen and fibrin D-dimer (coagulation markers), and serum levels of IL-6 (inflammation) were measured by ELISA in 30 patients with biopsy-proven breast cancer, 30 patients with biopsy-proven prostate cancer, and 30 ageand sex-matched controls for each group. Prostate specific antigen was also measured in the men. Release of VEGF from IL-6 stimulated platelets was assessed by ELISA. Plasma levels of IL-6 (P <0.02), VEGF, soluble P-selectin, fibrinogen, and fibrin D-dimer (all p <0.01) were significantly raised in breast cancer, whereas VEGF, soluble P-selectin, fibrin D-dimer (all p <0.01) and fibrinogen (p <0.05) were significantly raised in prostate cancer. Significant correlations were found between IL-6 and VEGF (p <0.01), and IL-6 and soluble P-selectin (p = 0.038) in breast cancer. Further experiments demonstrated an in vitro IL-6 induced dose-dependent release of VEGF from platelets. In conclusion, strong relationships between IL6 and VEGF, but not with coagulation or platelet markers, and release of VEGF from IL-6 stimulated platelets, suggest a role for inflammation and platelets in angiogenesis.
Keywords: Angiogenesis; cancer; interleukin-6; platelets; soluble P-selectin